The Effect Of Corporate Governance On Cash Holdings - Wirianata, Henny (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
This study was conducted to determine the influence of corporate governance in manufacturing companies in determining cash holdings accompanied by financial performance as a control variable. Corporate governance is measured from board structures proxied by board size, independent board compositions, and board meetings; the audit committee proxied by the number of members and meetings; and ownership structures are proxied with institutional and managerial ownership. The data in the study were taken by purposive random sampling. The data in the study was processed and analysed using panel data regression analysis using Eviews 10 for the 2017-2021 research period. The results showed that, partially, board size and the independent board compositions have a positive and significant influence. Meanwhile, board meetings, audit committee members, audit committee meetings, institutional ownership and managerial ownership did not significantly influence.